(untitled) (Zoo Botanica, 2025)
Medicinal plants are extensively utilized in various traditional medicinal systems owing to their wide range of pharmacological properties and minimal adverse reactions in living organisms. The study was aim to assesses the green synthesis and characterization of Copper oxide nanoparticle against Hetrotermes indicola and antibacterial activity. Utilizing plant extracts for the production of metal nanoparticles shows great potential as an environmentally sustainable synthesis approach. In particular, green synthesis of metal-based nanoparticles using medicinal plants represents a promising alternative to conventional chemical and physical methods. The study at hand amalgamated the medicinal attributes of Moringa oleifera and Syzygium cumini leaves, known for their termiticidal and antibacterial qualities to synthesize copper oxide nanoparticles (CuO-NPs), thereby creating a value-added, multifunctional, inorganic material. The preference for biological pathways in nanoparticle fabrication is steadily increasing due to factors such as cost-effectiveness, scalability, and environmental sustainability. In this context, a green synthesis method utilizing aqueous leaf extracts has been successfully employed to fabricate CuO-NPs. Additionally, the termiticidal efficacy of the CuO-NPs was evaluated through a bioassay approach. A comparison between two groups revealed a comparatively lower termiticidal impact with the CuO-NPs derived from S. cumini, whereas a significantly higher efficacy was observed with those from M. oleifera. This suggests that the phytochemicals present in M. oleifera may contribute more effectively to the synthesis of bioactive CuO-NPs with termiticidal properties. Green synthesized CuO-NPs from S. cumini have the largest zone of inhibition against Escherichia coli, indicating they are particularly effective against this bacterium while CuO-NPs from M. oleifera showed broad spectrum antibacterial activity with the highest inhibition against Bacillus cercus. These results highlight the selective efficacy of each extract-derived nanoparticle type against specific microbial strains. This study underscores the significant potential of green-synthesized CuO-NPs as effective termiticidal and antibacterial agents. These nanoparticles are capable of mitigating the harmful effects caused by H. indicola and exhibit antibacterial properties against various pathogenic strains. Overall, the findings advocate for the utilization of plant-based green synthesis methods in developing biofunctional nanomaterials for pest and microbial control.